2010
DOI: 10.1097/tp.0b013e3181fa93fa
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcineurin Inhibitors in the Outcome of Liver Transplantation in Hepatitis C Virus-Positive Recipients

Abstract: Baseline characteristics (demographics, liver function at LT, genotype distribution, donor, surgery, and IS except for the type of calcineurin inhibitor) did not differ between groups. Severe disease (defined as bridging fibrosis, cirrhosis, cholestatic hepatitis, or allograft loss or death because of recurrent disease in the first year) was present in 67 of 253 (26.5%) and was equally distributed in the CsA and Tac groups (27% vs. 26%; P=0.68). Two thirds of protocol biopsies performed at 1 year showed some f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 24 publications
2
46
2
Order By: Relevance
“…There was no significant difference in severity of HCV recurrence, SVR rates (in those 69 patients who received antiviral therapy), and graft and patient survival between CSA and TAC groups. 71 Recent meta-analyses suggested no difference in HCV recurrence between TAC and CSA regimens, but TAC increased graft and patient survival in HCV transplanted patients. 72 Interestingly, a synergistic role of CSA in combination with antiviral therapy has been suggested.…”
Section: Immunosuppressive Regimensmentioning
confidence: 99%
“…There was no significant difference in severity of HCV recurrence, SVR rates (in those 69 patients who received antiviral therapy), and graft and patient survival between CSA and TAC groups. 71 Recent meta-analyses suggested no difference in HCV recurrence between TAC and CSA regimens, but TAC increased graft and patient survival in HCV transplanted patients. 72 Interestingly, a synergistic role of CSA in combination with antiviral therapy has been suggested.…”
Section: Immunosuppressive Regimensmentioning
confidence: 99%
“…25 Although it was believed that tacrolimus did not have this property, a prospective study of 253 HCV-positive patients who underwent transplant showed that patients receiving cyclosporine or tacrolimus showed no significant differences in virologic and clinical outcomes. 26 In 71 HCV infected kidney transplant recipients who were on cyclosporine or tacrolimus, analysis of viral kinetics and liver fibrosis showed that HCV viral load was lower in patients treated with tacrolimus than cyclosporine, and this effect became negligible 3 months after transplant. The extent of liver fibrosis was similar in both groups of HCV infected patients and a control group of non-HCV-infected patients after kidney transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the prevention of rejection by obtaining and maintaining adequate levels of tacrolimus from the very early post-operative period is very important. Cyclosporine has been suggested to be superior to tacrolimus in controlling HCV recurrence post-transplant given the antiviral effects of cyclosporine in vitro but clinical trials failed to confirm this expectation and currently there is no evidence that the choice of CNI (cyclosporine or tacrolimus) makes a significant difference in outcome in HCV recipients (Berenguer et al, 2010). Antiviral therapy with interferon and ribavirin is an option in selected transplant recipients with recurrent HCV: progression to cirrhosis is slower, risk of graft decompensation is lower and patient survival is longer in responders to antiviral treatment compared to non-responders (Berenguer et al, 2008).…”
Section: Immunosuppression In Liver Transplantationmentioning
confidence: 99%